2014
DOI: 10.3354/meps10988
|View full text |Cite
|
Sign up to set email alerts
|

Balancing complexity and feasibility in Mediterranean coastal food-web models: uncertainty and constraints

Abstract: Mass-balance trophic models (Ecopath and EcoTroph) are valuable tools that can be used to describe ecosystem structure and functioning, identify target species to be monitored, and allow comparisons of ecosystem states under different management options. Nevertheless, the Ecopath modelling approach is constrained by 2 major sources of uncertainty: model complexity and input data quality. We developed an approach for identifying the optimum model structure that considers trade-offs between feasibility, complexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…, Prato et al. ). Being both a preferred prey for many high trophic level predators and predators acting on a wide range of trophic levels, cephalopods occupy an important functional role in both coastal and pelagic ecosystems (Piatkowski et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Prato et al. ). Being both a preferred prey for many high trophic level predators and predators acting on a wide range of trophic levels, cephalopods occupy an important functional role in both coastal and pelagic ecosystems (Piatkowski et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Prato et al. ), data quality was assessed applying the food web diagnostics proposed by Link () and the Data‐Reli toolbox developed by Lassalle et al. ().…”
Section: Methodsmentioning
confidence: 99%
“…Studies indicated that communication with stakeholders, particularly decision makers, should be encouraged before and during model development to ensure that ecosystem modelling work is tailored (1) to address relevant management objectives, questions and issues on the table, and (2) to facilitate the necessary buy-in and investment by decision makers into the process of producing scientific results for advising management. In this context, an interesting example was presented of how dialogue with the PortCross National Park (NW Mediterranean Sea) MPA managers is initiating improvements in terms of monitoring of key groups in MPA and stimulating keen interest and buy-in from the MPA managers (Prato et al 2014). Another example was provided in the context of management of marine resources in the Azores (Morato et al 2014), where managers obtained buy-in from fishers after they saw the improved catches due to closures for research purposes.…”
Section: Introductionmentioning
confidence: 98%
“…Conversely, Muto et al (2014) showed that mercury biomagnification can be used to trace trophic positions in species of the northern Brazilian continental shelf. As an example of how to integrate such information, Prato et al (2014) built a food web model of the NW Mediterranean using field-derived information. They show the effects of biological articulation on food web indicators and identify taxa of little commercial interest but high trophodynamic im portance.…”
Section: Novel Approachesmentioning
confidence: 99%
“…Sensitivity and uncertainty analysis (e.g. Pranovi et al 2014, Prato et al 2014 can test the robustness of trophodynamic models and identify key ecosystem elements (food web nodes, aggregation level; e.g. Jordán et al 2014) on which data collection needs to focus.…”
Section: Quantifying Trophodynamics Is Not Easymentioning
confidence: 99%